Lifesaving dose increment of cabergoline in life-threatening spontaneous ovarian hyperstimulation syndrome resistant to all interventions. (3rd April 2019) - Celik, Samettin; Soyer-Calıskan, Canan; Hatirnaz, Safak; Celik, Handan; Tosun, Miğraci; Hatirnaz, Ebru S.
Abstract: Objective: Spontaneous ovarian hyperstimulation syndrome (SOHSS) is an extremely rare complication that deserves a multidisciplinary approach together with a thorough investigation for the correct diagnosis of the underlying pathology. The aim of this study was to present a case of severe SOHSS resistant to all interventions and to discuss the available interventions to overcome such a rare and serious clinical situation. Case report: We report a case of severe, life-threatening spontaneous OHSS with a normal nine weeks singleton pregnancy in a 25-year-old nulliparous woman, which resulted with pregnancy termination and continuation of disease progression until the dose of cabergoline was increased to 1.5 mg/day. Conclusion: This case report emphasizes that patients with life-threatening SOHSS resistant to all medical and surgical interventions may benefit from higher doses of cabergoline. Although spontaneous OHSS is extremely rare, it is potentially a life-threatening clinical entity in its severe form and needs time management and detailed examination of the underlying causes.